2010
DOI: 10.1111/j.1365-2893.2010.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of GB virus type C/hepatitis G virus coinfection in patients with chronic hepatitis C undergoing antiviral therapy

Abstract: Coinfection with GBV-C/HGV in patients with chronic hepatitis C (CHC) may influence clinical course and response rates of antiviral therapy. Aim of the study was to investigate the prevalence of GBV-C/HGV/HCV coinfection and its influence on outcome of interferon/ribavirin combination therapy. Three hundred and four patients with CHC [m/f = 211/93, age: 42 (18-65)] were investigated. HGV RNA detection was performed by polymerase chain reaction prior to and 6 months after the end of antiviral therapy. HGV/HCV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
(68 reference statements)
2
4
2
Order By: Relevance
“…Third, HPgV-2 viremia was not as prevalent as HPgV-1 viremia in all of the groups tested (Table 1, S1 Table). We found HPgV-1 in 9.5% of HCV-infected individuals and in 4.2% of volunteer blood donors, comparable with other reports [24][25][26][27][28][29], while HPgV-2 viremia was 1.1% in HCV-infected individuals (p < 0.0001 versus HPgV-1 viremia) and absent in volunteer donors (p < 0.0001). This difference in prevalence may reflect differences in the mode or efficiency of HPgV-2 transmission relative to HCV and HPgV-1.…”
Section: Discussionsupporting
confidence: 80%
“…Third, HPgV-2 viremia was not as prevalent as HPgV-1 viremia in all of the groups tested (Table 1, S1 Table). We found HPgV-1 in 9.5% of HCV-infected individuals and in 4.2% of volunteer blood donors, comparable with other reports [24][25][26][27][28][29], while HPgV-2 viremia was 1.1% in HCV-infected individuals (p < 0.0001 versus HPgV-1 viremia) and absent in volunteer donors (p < 0.0001). This difference in prevalence may reflect differences in the mode or efficiency of HPgV-2 transmission relative to HCV and HPgV-1.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings were consistent with the previous reports in the patients with HIV/HCV coinfection from Australia (6) and Germany (5), suggesting a similar transmission efficiency for the three viruses among high risk group. Moreover, the higher prevalence of GBV-C RNA was 33.33% in our cohort with HCV mono-infection than other studies (16, 17). This might be explained by the impact of HCV treatment on GBV-C RNA clearance.…”
Section: Discussioncontrasting
confidence: 69%
“…Alvarado-Mora et al in Colombia reported that 5.06% of HBsAg-positive samples were also HGV-positive, while 3.2% of HCVpositive cases were HGV-positive (4), which in the case of HBV samples is close to our findings but much lower than the co-infection rate of HGV and HCV in the present study. Co-infection of HGV with HCV was reported as 12.2% by Hofer et al (20). In an investigation by Ziaee et al on hemodialysis patients in Birjand, Iran, 5% of HGV-infected patients also had HCV (21), much lower than our results.…”
Section: Discussioncontrasting
confidence: 56%